Structual adjustment program of IMF and World Bank - Mars, Hedi (KDI School, 2011)
This study aims to examine the effects of structural adjustment programs imposed by IMF and World Bank to Tunisian authority in order to stabilize the macroeconomic variables in the short run and to open the economy in order to integrate the world economy in the long run. Indeed Tunisia as a country in the process of development has been since its independence reliance on external financing. Indebtedness has been mastering and has continued adverse economic factors; it took such magnitude that the structural adjustment program makes it suggested by the IMF. The SAPs introduced in 1986 aimed, through sectoral reforms, to reduce aggregate demand and stimulates aggregate supply and thus reduces the persistent balance of payments deficit. Approval of international monetary fund to development countries and especially Tunisia has become more indispensable to enable them to rebuild their external accounts. The objective of my study is to analyze the economic situation of Tunisia before and after the implementation of structural adjustment programs which spread from 1986 to 1999. we proceed, to explain the origins and characteristics of SAPs suggested by the World Bank and IMF, first, and in the second part of the work we elaborate on the case of Tunisia, by using tables and graphs that illustrates the performance of macroeconomic variables in several areas after the introduction of sectoral reforms, the third part will be devoted to give an outlook to the Tunisian economy and if it has been integrated in the international economy and what should be done in order to ensure a full integration with a safe manner.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: IMF--World Bank